Public markets as spaces for the practice of non-hegemonic social subjects: the case of San Pedro in the city of Cuzco- Peru - Andrade, Rita de Cassia Gregorio de [UNESP]; Goes, Eda Maria [UNESP] (Univ Federal Fluminense, 2022)
In this work, we analyze the San Pedro Central Market, in the city of Cuzco - Peru and the practices of non-hegemonic social subjects in the production of urban space. The methodological procedures were bibliographic review, documental survey, interviews, and application of surveys with city locals. The object of this study is predominantly investigated by qualitative methodology. We aimed to study this market, as a space of production of non-hegemonic social subjects, the challenges facing the economic context and the influence of tourism in recent decades. Competition with commercial spaces, such as supermarkets, conflicts with the government and suitability for tourism were observed, which express contradictions between change and permanence, local and global.
Keywords: Public market; Non-hegemonic social subjects; Spatial practices; San Pedro Market; Cuzco-Peru